2013
DOI: 10.1002/bit.24809
|View full text |Cite
|
Sign up to set email alerts
|

Programmable mechanical stimulation influences tendon homeostasis in a bioreactor system

Abstract: Identification of functional programmable mechanical stimulation (PMS) on tendon not only provides the insight of the tendon homeostasis under physical/pathological condition, but also guides a better engineering strategy for tendon regeneration. The aims of the study are to design a bioreactor system with PMS to mimic the in vivo loading conditions, and to define the impact of different cyclic tensile strain on tendon. Rabbit Achilles tendons were loaded in the bioreactor with/without cyclic tensile loading (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
152
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(171 citation statements)
references
References 61 publications
10
152
2
Order By: Relevance
“…Bioreactors in tissue engineering [9] create a controlled and sterile environment for development of engineered tissues, including tendon [10]. Bioreactors designed to provide in vitro mechanical stimulation are thought to replicate physiologic conditions and promote cell differentiation and tenogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bioreactors in tissue engineering [9] create a controlled and sterile environment for development of engineered tissues, including tendon [10]. Bioreactors designed to provide in vitro mechanical stimulation are thought to replicate physiologic conditions and promote cell differentiation and tenogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although further research is required to elucidate the specific loading conditions (ie, magnitude, duration, frequency and rate) that maximise tendon adaptation, in vitro 1 2 and in vivo 3–6 evidence indicates tendon has an optimal range or ‘sweet spot’7 within which mechanical loading promotes positive tissue adaptation or homeostasis, with either too much or too little loading being detrimental (figure 1). In vitro bioreactor studies of rabbit Achilles tendon have shown that continuous 8 hours/day for 6 days of 6% cyclic strain at 0.25 Hz maintains1 and promotes2 tendon health, but the same duration and frequency with strain magnitude of 3% and 9% disrupted the extracellular matrix. Tendons that were load-deprived for 12 days increased their expression of collagen of inferior material properties (ie, type III) and had diminished mechanical performance.…”
mentioning
confidence: 99%
“…Although not represented in this figure, strain frequency, strain duration and strain rate also affect Achilles tendon adaptation. Figure adapted from Wang et al 1 and Pizzolato et al 7…”
mentioning
confidence: 99%
“…12 Eccentric exercises can reshape and enhance the tolerability of Achilles tendon by strengthening the fiber crosslink in the tendon. 13 A 5-year follow-up study 14 suggested that patients experienced a significant increase in the VISA-A scale scores after receiving eccentric exercises, whereas only a mild degree of pain remained. Another 5-year study 15 indicated that the overall efficacy rate was as high as 80%, whereas the recurrence rate was approximately 15%.…”
Section: Discussionmentioning
confidence: 99%